DEVELOPMENT OF PROFESSIONAL COMPETENCIES OF FUTURE PRIMARY SCHOOL TEACHERS IN THE PROCESS OF PEDAGOGICAL PRACTICE (Scientific journal of the Fergana State University, 2026)
This article explores the process of developing the professional competencies of future primary school teachers through pedagogical practice. Pedagogical practice plays a crucial role in testing students’ theoretical knowledge, familiarizing them with the content of teaching activities, developing methodological skills, and preparing them for independent work. The article analyzes the main components of professional competencies – methodological, communicative, reflective, organizational, and innovative. It also highlights the opportunities for professional growth through the use of didactic approaches, effective classroom management, and self-reflection. The results of the study contribute to the improvement of professional training for future primary school teachers.